Examining the predictors of willingness to seek counselling services - Tan, Yee Shin; Zakaria, Noor Syamilah; Subarimaniam, Neerushah (Human Resource Management Academic Research Society, 2021)
The state of adolescents’ mental well-being has reached an alarming and worrying stage. Adverse life events, patterns of family changes, changes in peer relationships, and accompanied by the emergence of mental health problems are significant factors influencing the development of psychosocial problems among adolescents. Unfortunately, only a small number of adolescents will go for formal sources such as professional counsellors or mental health professionals when they need help. Thus, the main purpose of the present study was to determine the relationships between parent-child connection, social support, and willingness to seek counselling services among secondary school students in a selected district in Selangor, Malaysia. A total of 437 respondents participated in the present study of which were selected through cluster sampling techniques. The findings demonstrated that motherchild regard, mother-child responsibility, father-child responsibility, and family social support were positively correlated with willingness to seek counselling services among secondary school students. This study concluded family social support as a significant predictor of willingness to seek counselling services. Our study would suggest the importance of counsellors to psycho educate the students about the access and functions of counselling services in schools.